Correlation of Spiritual Well-Being and Hopelessness In Leukemia Patients at District Peshawar Cancer Hospitals. - Nasir Anwar, Nasreen Ghani, Akhtar Zeb, Baseer Muhammad, Amir Sultan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Cancer is considered the most fatal diseases which is accountable for Cancer second leading cause of death in the developed country like United States and contributes to a high mortality rate in all age groups. Patient with cancer face life-threating situation through the period of diseases process. Aim: To explore the spiritual well-being and hopelessness among the leukemia patient and it correlation with each other. Methodology: A descriptive correlation design was used while patient with leukemia were the study participants and HMC and IRNUM were study setting. Sample size of the study was 320 while using consecutive sampling technique. Data was collected through two valid and reliable questionnaires of spiritual well-being and hopelessness, after the approval of study by IRB. Results: In the study majority of the participants were male 213(67%) and female 107(33%) In spiritual well-being the higher number of participants was moderate spiritual well-being (66%), followed by higher spiritual well-being (22%) and poor spiritual well-being (12%). The higher number of participant hopelessness were moderate (49%), then severe hopelessness (28%), and mild hopelessness (23%). Conclusion: The study concluded that there is a positive correlation between spiritual well-being and hopelessness. Spiritual and religious well-being is important to cope with these issues and improves quality of life. Keywords: Hopelessness, Cancer, spiritual well-being, leukemia